Reclaiming Canadian Bodies : Visual Media and Representation - Mannik, Lynda, 1957-; McGarry, Karen, 1972- (Book collections on Project MUSE., 2015)
The central focus of Reclaiming Canadian Bodies is the relationship between visual media, the construction of Canadian national identity, and notions of embodiment. It asks how particular representations of bodies are constructed and performed within the context of visual and discursive mediated content. The book emphasizes the ways individuals destabilize national mainstream visual tropes, which in turn have the potential to destabilize nationalist messages. Drawing upon rich empirical research and relevant theory, the contributors ask how and why particular bodies (of Estonian immigrants, sports stars, First Nations peoples, self-identified homosexuals, and women) are either promoted and upheld as "Canadian" bodies while others are marginalized in or excluded from media representations. Essays are grouped into three sections: Embodied Ideals, The Embodiment of "Others," and Embodied Activism and Advocacy. Written in an accessible style for a broad audience of scholars and students, this volume is original within the field of visual media, affect theory, and embodiment due to its emphasis on detailed empirical and, in some cases, ethnographic research within a Canadian context